Chelation of mercury intoxication and testing different protective aspects of Lactococcus lactis probiotic in African catfish. (23rd March 2021) - El‐Bouhy, Zeinab M.; Reda, Rasha M.; Mahboub, Heba H.; Gomaa, Fify N.
Abstract: The current study aimed primarily to test various probiotics ( Lactococcus lactis ( L. lactis ), Enterococcus faecalis, Lysinibacillus sp., Citrobacter freundii, Bacillus subtilis, Bacillus amyloliquefaciens, Bacillus cereus, Citrobacter freundii and Leuconostoc mesenteroides ) against 10, 20 and 30 ppm of mercury (Hg). The most efficient probiotic upon applying MIC was L. lactis (33HT) that tested for ameliorating the Hg toxicity and investigated its influence on haematology, immunity, biochemical parameters and bioaccumulation. African catfish ( n = 180) were divided into six equal groups including control (CT) fed a basal diet; supplemented basal diet with 10 9 and 10 10 CFU/g of L. lactis, ( L. lactis 9) and ( L. lactis 10); control positive group (Hg) offered a basal diet incorporated with 0.13 ppm of Hg; Hg+ L. lactis 9 and Hg+ L. lactis 10 which received Hg (0.13 ppm) plus the same treatment of the 2nd and 3rd groups. Results clarified that the dietary additive of L. lactis improved the haematological picture and revealed a significant increase in lysozyme, antiprotease activity, nitric oxide, GSH, MDA, total protein, albumin and globulin. Besides modulating ALT, AST, urea and creatinine levels compared with other groups. The results propose the potential use of L. lactis to ameliorate Hg toxicity and as an immune stimulant.